Detection of banned antibacterial growth promoter in animal feed by enzyme-linked immunosorbent assay: Method validation according to the Commission Decision 2002/657/EC criteria. (January 2015) - Squadrone, Stefania; Marchis, Daniela; Loria, Andrea; Amato, Giuseppina; Ferro, Gian Luca; Abete, Maria Cesarina
Abstract: An enzyme-linked immunosorbent assay (ELISA) test has been applied for the qualitative screening analysis of virginiamycin and bacitracin in feedingstuffs at level of 1 mg/kg. The ELISA validation study was performed according to the Commission Decision 2002/657/EC criteria established for qualitative screening methods in food. In this regard, the following parameters were determined: detection capability (CCβ), specificity and ruggedness. The resulted CCβ values were <1 ppm for both molecules and no interferences from matrix effects were observed. Slight variations of some critical factors in the sample pre-treatment and clean up were deliberately introduced for ruggedness evaluation and they did not result in any negative effect on the detection of virginiamycin, while ruggedness evaluation on the detection of bacitracin showed some critical factors. The proposed method is suitable for qualitative screening analysis of virginiamycin and bacitracin in conformity with the current EC performance requirements. Highlights: Bacitracin and virginiamycin were banned from animal feed in 1998 (2821/98/UE). An ELISA validation study was performed according to 2002/657/UE criteria. The resulted CCβ values were <1 ppm. No interferences due to matrix effects were observed.